PENINGKATAN KINERJA KARYAWAN BERBASIS KOMPENSASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA PADA LEMBAGA PENYIARAN PUBLIK TVRI SUMATERA UTARA MEDAN - Izmi Maghfira Maghfira; Asrizal Efendy Nasution (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to determine and analyze the effect of compensation, work environment and work discipline on the employee performance of TVRI Public Broadcasting Institute, North Sumatra, Medan. The population in this study were all employees of TVRI Public Broadcasting Institute, North Sumatra, Medan, amounting to 62 people. Sampling using the saturated sample method, namely by using the entire existing population as a sample. Data collection techniques in this study by means of documentation studies and the distribution of questionnaires. The data analysis technique used multiple linear regression, classical assumption test, hypothesis testing and coefficient of determination.The results showed that partially there was no significant effect of compensation on the employee performance of TVRI Public Broadcasting Institute, North Sumatra, Medan. Partially, the work environment and work discipline have a significant effect on the employee performance of TVRI Public Broadcasting Institute, North Sumatra, Medan. Simultaneously, the factors of compensation, work environment and work discipline showed a significant influence on the employee performance of TVRI Public Broadcasting Institute, North Sumatra, Medan. Keywords: Compensation, Work Environment, Work Discipline, Employee Performance